Pengaruh Cash Holding, Modal Kerja dan Tax Planning terhadap Kinerja Keuangan dengan Komisaris Independen sebagai Pemoderasi - Frangky Yosua Sitorus; Angelene Quintina; Swanto Sirait (Media Akuntansi Perpajakan, 2026)
This study aims to analyze the effect of cash holding, working capital, and tax planning on financial performance, with independent commissioners as moderating variables in these relationships. The research objects are energy sector companies listed on the Indonesia Stock Exchange during the 2022–2024 period, consisting of 34 companies with a total of 102 observations. The method used is panel data regression with a fixed effect model approach and robust standard error testing to address heteroscedasticity and autocorrelation issues. The results show that cash holding has a significant positive effect on financial performance, while working capital and tax planning do not have a significant effect. These findings suggest that efficient cash management improves financial flexibility and profitability, whereas working capital and tax planning have not been effectively optimized. Independent commissioners are proven to strengthen the influence of cash holding and tax planning on financial performance but do not moderate the relationship between working capital and financial performance. This research highlights the importance of good corporate governance in maximizing firm value through effective oversight of internal financial management.